Prevalence of Electronic Cigarette Use Among University Students: Predictors and Mediators - Mete, Burak; Uysal, Merve; Demirhindi, Hakan; Çetinkaya, Pelin Duru (Addicta: The Turkish Journal on Addictions, 2024)
Abstract: This study aimed to determine the prevalence and factors affecting the use of electronic cigarettes among university students. This cross-sectional study included 987 participants. The prevalence of electronic cigarette use among students was 5.4%, and the prevalence of trying electronic cigarettes at least once was 26.3%. Nicotine dependence levels of students who smoked electronic cigarettes were significantly high. Everyday electronic cigarette smokers commonly perceive traditional cigarettes to be more harmful. The rates of electronic cigarette use were significantly higher in males, those with high household income, those with a family history of traditional or electronic cigarette smoking, those who had smoked traditional cigarettes at least once in their lives, and those who were everyday cigarette smokers. Male sex and family history of electronic cigarette use were direct and effective predictors of everyday electronic cigarette use. The risk of everyday electronic cigarette use increased 7.91 times in the presence of electronic or traditional cigarette smokers in the family and 4.66 times in the presence of e-cigarette users in the family. The rates of electronic cigarette use and attempted electronic cigarette use were found to be high among university students. Awareness training and increased inspections and sanctions on the places where electronic cigarettes were purchased might prevent the growth of this problem.